Photocatalytic activity of CeO2 nanoparticles: synthesis using artocarpus gomezianus fruit mediated facile green combustion method - R. ANITHA; K.V. RAMESH; K.H. SUDHEERKUMAR (International Journal of Pharma and Bio Sciences, 2017)
Environment friendly and economical synthesis of nanoparticles can be achieved with the use of abundantly available natural products. Cerium Oxide nanoparticles have been proven to be competent photo catalysts for environmental applications because of their strong redox ability, nontoxicity, long-term stability and low cost. This report explain the synthesis of CeO2 nanoparticles via eco-friendly green combustion method using Cerium nitrate as an oxidizer and citrate containing Artocarpus gomezianus fruit extract as a fuel at 400 0C. The photo-catalytic activity of these CeO2 nanoparticles was studied with the photo-degradation of model dye methylene blue under UV light irradiation. Interestingly, the photo catalytic properties of the CeO2 nanoparticles were found to degrade 5 ppm concentration of methylene blue with the time span 130 minutes. The study successfully demonstrated synthesis of CeO2 nanoparticles by simple ecofriendly route employing Artocarpus gomezianus extract as fuel that exhibit superior photodegradative activities.